2008
DOI: 10.1007/s00417-008-0898-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined intravitreal triamcinolone injection and laser photocoagulation in eyes with persistent macular edema after branch retinal vein occlusion

Abstract: Macular edema after BRVO can effectively be treated by a combination of intravitreal TA injection and subsequent laser photocoagulation. During a 6-month follow-up this combination treatment resulted in a significant reduction of central foveal thickness and improvement of visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
1
11
0
2
Order By: Relevance
“…The higher variability of VA outcome in cystoid ME was attributed to an increased inner anatomical disintegration because of compression and the interrupted connections of the retinal neuronal tissue. In line with our data, a significant CMT improvement has been reported in several studies for both bevacizumab- and TA-treated patients [14,15,16,17,18,19,21,22,23,27]. …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The higher variability of VA outcome in cystoid ME was attributed to an increased inner anatomical disintegration because of compression and the interrupted connections of the retinal neuronal tissue. In line with our data, a significant CMT improvement has been reported in several studies for both bevacizumab- and TA-treated patients [14,15,16,17,18,19,21,22,23,27]. …”
Section: Discussionsupporting
confidence: 80%
“…In a prospective study, Cakir et al [21] found no statistically significant increase in mean BCVA in 12 eyes who had failed to benefit from previous grid laser therapy according to the BRVO study guidelines at the 1 year follow-up. Riese et al [22] described a median BCVA improvement of 2 lines at 6 months of TA treatment (mean: 1.1 injections) followed by laser photocoagulation. Only Yepremyan et al [23] found a higher increase in BCVA in 12 eyes from an initial 0.13 to 0.32 (equals 4.1 lines) with a mean of 1.8 TA injections after an average of 15.3 months[,] and Özkiris et al [24] reported on a mean increase from 0.1 to 0.24 (equals 4.1 lines) after a mean of 1 TA injection at a mean follow-up of 6.2 months.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of IVTA with grid laser photocoagulation has been proposed, obtaining positive outcomes [77,78,79]. On the other hand, the combined treatment with IVTA and intravitreal bevacizumab has been tested [80,81].…”
Section: Treatmentmentioning
confidence: 99%
“…Recently, there have been two reports [252,253] from different departments showing an encouraging effect of IVTA combined with laser photocoagulation in eyes with macular edema after BRVO. In the report by Riese et al [252], at 6 months after treatment, a gain of 1 or more logarithmic lines was achieved in 16/24 eyes (67%) and a gain of 3 lines or more was achieved in 8/24 eyes (33%), and the median central foveal thickness decreased from 423 µm at baseline to 266 µm (p = 0.001).…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemamentioning
confidence: 99%